Reducing the Number of Germs on Hands Using Disinfectants Combination of Betal Leaves and Kalamansi Orange - Iwan Iskandar; Hevi Horiza; Mutia Yuhesti (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
Covid-19 can be spread through particles from a patient's sneeze or cough attached to other objects such as clothing or electronic devices from people around him. Therefore, it is necessary to take precautions to prevent the spread of Covid-19. There are many ways to prevent the transmission of Covid-19, one of which is the use of antiseptics and disinfectants. We can make disinfectants from natural ingredients such as boiled betel leaves and lime juice. Both of these plants have compounds that function as anti-microbial. From the results of the study, it was found that of the 3 combination formulas of Betel and Kalamansi, the best formula for reducing the number of germs was formula 2, namely the combination of Betel and Kalamansi with a ratio of 60:40. For testing against the nCov-2019 Virus, the best formula is formula 3, namely the combination of Betel and Kalamansi 40:60 with the results of 30 positive samples, 20 samples being negative due to damage to the glycoprotein envelope layer.